Discrepancies in Perceived Indulgent Parenting, Relationship Satisfaction, and Psychological Well-Being of Adolescents and Parents - Qinglan Feng; Ming Cui (MDPI AG, 2024)
Indulgent parenting has been associated with adolescents' psychological well-being problems; however, prior research has primarily relied on adolescents' report of such parenting behavior and its association with their own well-being, often overlooking parents' perceptions of indulgence and their own well-being. In this study, we address this gap in the literature by examining the agreement and disagreement between parents' and adolescents' perceptions of indulgent parenting and the implications for the psychological well-being of both adolescents and their parents. Further, we explore the role of adolescent-parent relationship satisfaction as a potential factor affecting these associations. Our investigation was based on data from 128 parent-adolescent dyads. Utilizing structural equation modeling with double-entry intraclass correlations (ICC_DE), our analyses revealed several main findings: (1) adolescents perceived higher levels of indulgent parenting than their parents did; (2) disagreement in perceived indulgent parenting between parents and adolescents was linked to psychological well-being problems for both adolescents and their parents; and (3) disagreement in perceptions in indulgent parenting had a stronger association with adolescents' well-being problems when adolescents reported greater relationship satisfaction with their parents. These findings provide insights into perceptions of indulgent parenting within parent-adolescent relationships and bring psychological implications for both adolescents and their parents.